EDUKASI DAN LATIHAN KESEIMBANGAN PADA LANSIA UNTUK MENCEGAH JATUH DI POSYANDU BAROKAH - Ratna Lestari; Dewi Utari (Jurnal Pengabdian Masyarakat, 2025)
Elderly as vulnerable groups value their independence, and falls can limit their ability to do activity significantly. More than one third of people age 65 and older falls every year and that condition can be repeated. Falls in the elderly are a common health problem experienced by the elderly, a vulnerable group. This is related to changes in the neuromuscular system, which can lead to decreased muscle strength and balance disorders. This community service program aims to provide an understanding of the risk of falls in the elderly and to improve their skills in preventing falls through balance training. Before the educational activity began, a fall risk screening was conducted using the TUGT instrument and the results showed that the majority of elderly people were in the low fall risk category with an average TUGT value of 9.4 seconds (<10 seconds). The activity continued with education on fall risks and prevention conducted through a lecture method equipped with booklet media. Meanwhile, balance exercises were taught using a demonstration method. This activity involved 23 elderly people. Before the education was given, the average pretest score obtained from the 23 elderly people was 71.9%, while after being given the education there was an increase in the posttest score to 94%. The results of observations made during the balance training were that 5 elderly people (21.7%) experienced difficulty in performing crosswalk movements and walking on heels and toes such as instability and feeling unsteady. Although the results of the fall risk screening tended to be low, balance exercises need to be carried out routinely by the elderly so that fall prevention can be carried out early.